Digger the Dinosaur - Dotlich, Rebecca Kai (I can read book., 2011)
"Digger wants to play baseball with his friends. But he isn't allowed to go out until he's cleaned his room. Digger starts cleaning at top speed, but the faster he moves the messier his room gets. His big tail and big feet aren't helping! Will Digger win the race to tidy his room and get to the game on time?"--Publisher's statement on Amazon.com.